Voltage Differencing Gain Amplifier-Based nth-Order Low-Pass Voltage-Mode Filter - Taskiran, Zehra Gulru Cam; Sedef, Herman; Anday, Fuat (WORLD SCIENTIFIC PUBL CO PTE LTD, 2018)
In this paper, a new active-C filter realizing the general nth-order low-pass voltage transfer functions using n voltage differencing gain amplifiers (VDGAs) is presented. In this realization minimum number of equal-valued grounded capacitors and n active elements are used. Due to the adjustability of the transconductance of the VDGA with current, different gains can be realized using the same building block and a simple filter structure can be created. The filter which is composed of VDGA building blocks is suitable for integration and advantageous in terms of eliminating parasitic effects because all capacitors are grounded and the filter structure has no resistors. All simulations are performed on SPICE and the accuracy of this method is validated experimentally with commercially available products upon on-board circuit.
Keywords: Voltage differencing gain amplifier (VDGA); filter synthesis; signal-flow graph; low-pass filter; FLOW GRAPH APPROACH; ACTIVE REALIZATION; CMOS REALIZATION; BIQUAD FILTER; CCII+; Computer Science; Engineering